How do you solve 10x – 8 + 2x(3) = 4(x – 8)+ 9(3 – x)? Algebra Linear Equations Multi-Step Equations with Like Terms 1 Answer Kalit Gautam Apr 25, 2018 Bring the constant and variables terms together :- Explanation: 10x – 8 + 2x(3) = 4(x – 8)+ 9(3 – x) rArr 10x+6x-4x+9x=-32+27+8 rArr 21x=3 :.x=1/7 Answer link Related questions How do you solve multi step equations by combining like terms? How do you solve multi step equation w + w + 12 = 40? How do you solve 3p + 4p + 37 = 79? How do you solve for f: f-1+2f+f-3=-4? How do you combine like terms? How do you combine like terms for -7mn-2mn^2-2mn + 8? How do you combine like terms for 3x^2 + 21x + 5x + 10x^2? What is a term? How do you solve 3v+5-7v+18=17? How do you solve for x in 5x + 7x = 72? See all questions in Multi-Step Equations with Like Terms Impact of this question 2269 views around the world You can reuse this answer Creative Commons License